PENGARUH LIKUIDITAS, AKTIVITAS, PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA (BEI) - Desi Aramana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Increasingly high business competition requires companies to pay attention to fundingmanagement to ensure the availability of capital, so that growth and increase inmarket share can run well. The aims of this study is to examine the effect of CR, TATO,ROA, and sales growth on capital structure. The population is 72 consumer goodsindustrial companies that go public and the sample used is 18 companies usingjudgment sampling technique with associative research methods. The results showedthat simultaneously, CR, TATO, ROA, and Sales Growth had an effect on the capitalstructure. Partially TATO, and sales growth affect the capital structure, while CR andROA have no significant effect. The company management should consider CR, ROA.This is because the company must determine the ratio of the amount of debt and itsown capital so that the optimal capital structure can be achieved. This method is doneby considering factors such as liquidity (current ratio), profitability (return on assets),and sales growth.